1993
DOI: 10.1111/j.1748-1716.1993.tb09598.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol on hippocampal neurons depends on their behavioural specialization

Abstract: Acute effect of ethanol on hippocampal neurons was studied during food acquisition behaviour in seven rabbits. The rabbits were taught to acquire food from a feeder by pressing a pedal on the same side of the cage. The behaviourally specialized units (L units related to newly learned behaviour and M units related to behaviour formed before learning, e.g. certain movements) were comparable with the 'place' (projectional pyramidal and granular cells) and 'displace' (non-pyramidal interneurons) units of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…From the traditional point of view, this would be understandable if the fibers were not afferent, but efferent ones. However, all the observed effects of the closure of the eyes were typical of afferent fibers of the optic tract (i.e., for the retinal ganglion cells; for detailed classification criteria, see Alexandrov et al, 1986). Why are there Efferent Influences in the Periphery? Activity of the retinal ganglion cells in darkness is quite a common phenomenon (Witkovsky, 1971).…”
Section: Behaviorally Related Activations Of Peripheral Neuronsmentioning
confidence: 98%
See 1 more Smart Citation
“…From the traditional point of view, this would be understandable if the fibers were not afferent, but efferent ones. However, all the observed effects of the closure of the eyes were typical of afferent fibers of the optic tract (i.e., for the retinal ganglion cells; for detailed classification criteria, see Alexandrov et al, 1986). Why are there Efferent Influences in the Periphery? Activity of the retinal ganglion cells in darkness is quite a common phenomenon (Witkovsky, 1971).…”
Section: Behaviorally Related Activations Of Peripheral Neuronsmentioning
confidence: 98%
“…For example, the retinal "darkness light," is considered as a necessary factor in proper functioning of the central neurons; its absence would mean "natural deafferentation" of the central areas (Granit, 1955 Because we observed behavior-related activations in the neurons of the visual cortex even when the animal's eyes were closed, it might be supposed that the absence of specific stimulation does not necessarily lead to deafferentation, but peripheral visual neurons could serve central units by producing behaviorrelated activations even without external influences. To examine this possibility, Alexandrov, Grinchenko, Shvyrkov, Jarvilehto, and Soininen (1986) recorded activity of the fibers in the central part of the optic tract2 in rabbits performing the food-acquisition task with open eyes and with eyes closed by nontransparent cups.…”
Section: Behaviorally Related Activations Of Peripheral Neuronsmentioning
confidence: 99%
“…Ethanol inhibits the induction of LTP in the hippocampus both in vitro (Morrisett & Swartzwelder, 1993) and in vivo (Givens & McMahon, 1995), and this effect is enhanced by stress (Talani, Biggio, & Sanna, 2011). The disruption of hippocampal cells by ethanol has been shown to be dose-dependent and temporary (White & Best, 2000) and to differentially affect specific cell types within the hippocampus (Alexandrov Yu et al, 1993). Changes in GABA and NMDA neurotransmission are also seen in the amygdala following ethanol consumption (Roberto, Gilpin, & Siggins, 2012), suggesting that LTP in this region is also disrupted.…”
Section: Alcohol and Fear Conditioningmentioning
confidence: 99%
“…In our previous studies, different types of neuronal specializations were identified in various brain areas of freely moving rabbits engaged in instrumental food‐acquisition behaviour (FAB) in a cage equipped with two pedals and two feeders (Alexandrov et al . 1990a, b, 1991, 1993, 1994, 2000a, b). The diverse types of specializations can be classified into two main categories: ‘M‐’ and ‘L‐neurones’.…”
mentioning
confidence: 99%
“…1976, Shvyrkov 1986, Alexandrov et al . 1990b, 1991, 1993, 1994, 2000a, b). In the present study, unit recordings were carried out from the area 29d of the cingulate cortex in freely moving rabbits.…”
mentioning
confidence: 99%